2012
DOI: 10.1007/s00436-012-2964-0
|View full text |Cite
|
Sign up to set email alerts
|

Acaricidal activity of eugenol on Rhipicephalus microplus (Acari: Ixodidae) and Dermacentor nitens (Acari: Ixodidae) larvae

Abstract: The aim of this study was to evaluate the acaricidal activity of eugenol, with different solubilizations and concentrations, on Rhipicephalus microplus and Dermacentor nitens larvae and to determine the lethal time. The study consisted of four experiments, and the mortality was assessed using the larval packet test with adaptations. The mortality observed in the first experiment was 100 % for all the groups treated with eugenol solubilized in different solvents. In the second, the hydroethanolic formulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(30 citation statements)
references
References 28 publications
3
25
0
2
Order By: Relevance
“…The acaricidal effects of thymol, carvacrol and eugenol in R. microplus and R. sanguineus larvae have been demonstrated in previous studies (Monteiro et al , ; Senra et al , , ). Furthermore, Novato et al () demonstrated that the association of carvacrol + thymol at certain concentrations had synergistic effects in A. sculptum and D. nitens larvae.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…The acaricidal effects of thymol, carvacrol and eugenol in R. microplus and R. sanguineus larvae have been demonstrated in previous studies (Monteiro et al , ; Senra et al , , ). Furthermore, Novato et al () demonstrated that the association of carvacrol + thymol at certain concentrations had synergistic effects in A. sculptum and D. nitens larvae.…”
Section: Discussionsupporting
confidence: 57%
“…Previous investigations of the effects of eugenol (Monteiro et al , ), thymol (Scoralik et al , ) and carvacrol (Senra et al , ) alone against R. microplus have demonstrated high larval mortality (near or equal to 100%) starting from the lowest concentrations tested. The same was observed by Senra et al () with carvacrol and eugenol, and by Daemon et al () with thymol in R. sanguineus s.l.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This has since been confirmed in other parasitic mites (Pasay et al., re; Sarcoptes scabiei var. suis ) and in multiple tick species of veterinary significance (de Monteiro et al., re: Rhipicephalus microplus and Dermacentor nitens ). According to the results presented, however, both geraniol and citral can also be considered as ‘active’ against D. gallinae .…”
Section: Discussionmentioning
confidence: 99%
“…Plant extracts are insoluble in this solvent thus only a limited number of scientists used this test for evaluation of efficacy. However, some workers modified LPT and have used acetone, ethanol and methanol in place of trichloroethylene (de Monteiro et al, 2012;Singh et al, 2015). Only condition of the solvent is that it should not cause mortality of tick's larvae more than 5% in control group.…”
Section: Plants Used As Acaricidesmentioning
confidence: 99%